Appropriating John Stott’s Concept of Holy-Worldliness towards Reformulating the Political Curriculum of Christianity in Africa - Gentleman Dogara (African Theological Journal for Church and Society)
This study appropriates John Stott’s concept of “holy-worldliness” to God’s call upon Christians from the world, and sending them out to be immersed in the affairs of the world as Christ’s ambassadors, by localizing Christ’s political curriculum to Africa. Examples of this localizing process were generated from Nigeria. Two research questions guided this study. Question 1: How can John Stott’s Concept of Holy-Worldliness be appropriated, towards reformulating the Political Curriculum of Christianity in Africa, using examples from Nigeria? Question 2: How can John Stott’s Concept of Holy-Worldliness be appropriated, towards solidifying the Political Curriculum of Christianity in Africa, using examples from Nigeria? The study concludes by calling Africa Christians to consider establishing one “African Christian School of Politics and Governance”, on the auspices of theological schools in Africa. This school would be mandated to drill African Christian politicians at the highest levels of the Political Curriculum of Christianity in Africa.